THE EFFECT OF FINANCIAL LITERACY AND EWOM TOWARDS PURCHASING DECISION COSMETIC PRODUCT ACROSS TWO GENERATION - Diar Rizki Fitriani; Irni Rahmayani Johan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The ease of information related to a cosmetic product through electronic word of mouth and financial literacy owned by millennial and Z generations can trigger purchasing decisions. The purpose of this study was to analyze the effect of financial literacy and electronic word of mouth on purchasing decisions in millennial and Z generations. The study used an explanatory research study design and voluntary sampling technique with a total of 122 millennial and Z generation respondents in Indonesia. Based on the results of the research, both generations have financial knowledge and financial attitudes in the low category, and the millennial generation's financial behavior are in the high category and generation Z is in the medium category. The electronic word of mouth variable is in the low category and generation Z's purchasing decisions are in the medium to high category and the millennial generation are in the medium category. Regression test shows that the education, financial literacy have a significant negative effect on purchasing decisions, while electronic word of mouth has a significant positive effect on purchasing decisions. The government and related stakeholders need to provide education related to financial literacy and sort out the right information about a product.